Desarrollo tecnológico a escala laboratorio de un sistema de mezclado y filtrado de crudo de almidón proveniente de granos semilla de la especie Chenopadium Quinua (Wild) (2016)
Initially, it has been made the state of the art taking into account the historical context and the current state of quinoa seed was performed to determine the problems to which solution with the design of the machine would. With the problems the functional requirements and design parameters were determined resource availability. Subsequently, three alternatives were proposed to give a solution to the problem before stipulated based on the functional requirements, design parameters and availability of resources, where by the method of linear weighting given 1 solution to a problem of multi-criteria. Performing this method alternative 1 was chosen, which is a decanter centrifuge system since gained more weight.